Analyzing language errors in mathematics Electronic School Book - Edhy Rustan; Mujahidin Mujahidin (Universitas Ahmad Dahlan, 2021)
This study aims to describe and categorize the types of language errors in the Class VII Mathematics Electronic School Book (BSE). The content analysis is a design chosen through a qualitative descriptive approach. The data source comes from BSE Mathematics Class VII. Data in the form of language errors related to speech errors, rules, and word choices in the Mathematics Electronic School Book. Data were collected using identification and categorization techniques in the corpus table. This study shows 43 language errors identified in BSE, consisting of 12 lapses, 21 errors, and ten mistakes. The results of this study become input for improving the use of language in electronic school books so that users can easily understand the meaning conveyed.